Wycena wartości niematerialnych i prawnych z wykorzystaniem opcji realnych - Góralski, Bartosz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Intangible assets are influencing managers to change the way of doing business. The processes inside corporations determine attitude towards employees, product development, service sales, and communication with customers. These fundamental changes are affecting strategies, reputation, short and long term decisions. The drivers of the value of companies are leaning toward intangible assets and force managers to develop new methods of their measurement and presentation. This article is focused on valuation of intangible assets exploiting the real option theory which improve the traditional, static valuation into dynamic foresee of intangible's value change. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1178, s. 25-38